2022
DOI: 10.1021/acs.orglett.2c00602
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Stereoselective Synthesis of 2,3-Diglycosylindoles and Tryptophan-C-glycosides via Palladium-Catalyzed C–H Glycosylation of Indole and Tryptophan

Abstract: We described a novel palladium-catalyzed C−H glycosylation of indole or tryptophan for a one-pot stereoselective synthesis of 2,3-diglycosylindoles and tryptophan-C-glycosides. In this strategy, the use of air and base-free and ligand-free conditions provided a highly efficient route to construct C-glycosides. The method can be applied to a wide range of cost-effective and convenient glycosyl chloride donors. Mechanistic studies indicated that the indole 2,3-diglycosylation sequence was C3 and then C2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…7a Recently, the Liu and Liang groups reported palladium-catalyzed C−H glycosylation of indole or tryptophan for the synthesis of 2,3-diglycosylindoles and tryptophan-C-glycosides using N-linked pyrimidine-containing directing groups (Scheme 1b). 12 Especially, upon complexation of Pd by the ester or phthalimide groups, the directed remote C−H glycosylation of more complex tryptophan substrates did not proceed well. Recently, the stereoselective synthesis of C-α-mannosyl tryptophan was attained by the use of isoquinoline auxiliaries installed on the N-terminus 7a or N-linked auxiliaries 12 with simple mannosyl chloride donors.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…7a Recently, the Liu and Liang groups reported palladium-catalyzed C−H glycosylation of indole or tryptophan for the synthesis of 2,3-diglycosylindoles and tryptophan-C-glycosides using N-linked pyrimidine-containing directing groups (Scheme 1b). 12 Especially, upon complexation of Pd by the ester or phthalimide groups, the directed remote C−H glycosylation of more complex tryptophan substrates did not proceed well. Recently, the stereoselective synthesis of C-α-mannosyl tryptophan was attained by the use of isoquinoline auxiliaries installed on the N-terminus 7a or N-linked auxiliaries 12 with simple mannosyl chloride donors.…”
mentioning
confidence: 99%
“…12 Especially, upon complexation of Pd by the ester or phthalimide groups, the directed remote C−H glycosylation of more complex tryptophan substrates did not proceed well. Recently, the stereoselective synthesis of C-α-mannosyl tryptophan was attained by the use of isoquinoline auxiliaries installed on the N-terminus 7a or N-linked auxiliaries 12 with simple mannosyl chloride donors. The limitation of this approach is that the removal of the isoquinoline directing group needs strong acid.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Metal-catalyzed coupling reactions have provided powerful modern tools for C -glycoside synthesis . Over the past few years, metal-catalyzed C – H glycosylation reactions have emerged as a new strategy for the synthesis of C -glycosides, enabling more streamlined retrosynthetic disconnections. In the previous studies, we and others showed that amide-linked bidentate auxiliaries can direct C – H glycosylation with glycosyl chloride donors under palladium catalysis . Liang recently reported that the aminoquinoline auxiliary can facilitate ortho C – H glycosylation of arenes with chloride donors using nickel catalysts (Scheme B) .…”
mentioning
confidence: 99%